2010
DOI: 10.1007/s12156-010-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of high-risk groups for breast and ovarian cancer in Europe: a focus on the Jewish population

Abstract: Low breast cancer screening rates are often found among ethnic minority groups and those born outside the host country. This is of particular concern for high-risk groups, who should benefit from ongoing trials aimed at optimizing screening strategies for breast, as well as ovarian cancer. Both of these issues are germane for Jewish women in Europe. We systematically review the literature concerning breast cancer early detection practices (BCEDP) among Jewish women, and examine European surveillance studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 154 publications
(267 reference statements)
2
17
0
Order By: Relevance
“…"hallmarks of cancer" [28] can potentially be revealed [29]. For almost two decades, it has been suggested that MRS could be the method of choice for early ovarian cancer detection [30,31]. That potential has not yet been realized, however, due mainly to the limitations of the manner in which MRS time signals are analyzed.…”
Section: The Clinical Problem: the Need For Accurate And Timely Detecmentioning
confidence: 99%
See 1 more Smart Citation
“…"hallmarks of cancer" [28] can potentially be revealed [29]. For almost two decades, it has been suggested that MRS could be the method of choice for early ovarian cancer detection [30,31]. That potential has not yet been realized, however, due mainly to the limitations of the manner in which MRS time signals are analyzed.…”
Section: The Clinical Problem: the Need For Accurate And Timely Detecmentioning
confidence: 99%
“…Among these are areas of cancer diagnostics where in vivo MRS would be of greatest added value. We have highlighted early ovarian cancer diagnostics, where for nearly two decades, as noted, the need for an effective in vivo MRS-based screening method has been underscored [30,31]. We proceed now to succinctly review the course of applications of in vivo MRS to the ovary, starting with conventional Fourier processing and then with the fast Padé transform.…”
Section: Spectra Averagingmentioning
confidence: 99%
“…Taking this wider view motivates efforts to garner maximal diagnostic information from MRS. One priority area is early ovarian cancer diagnostics, where the need for an effective in vivo MRS-based screening method has been underscored for many years [19][20][21]. While technological progress is obviously important, mathematical advances in signal processing are the most critical for MRS, as we will demonstrate.…”
Section: Implications For Cancer Diagnosticsmentioning
confidence: 99%
“…Among these are areas of cancer diagnostics where in vivo MRS could potentially have the greatest added value. We have singled out early ovarian cancer diagnostics, where the need for an effective in vivo MRS-based screening method has been highlighted for nearly two decades [58,76,96]. …”
Section: Iterative Averaging: a Stabilization Procedures Through The Fptmentioning
confidence: 99%